Comparison of Oil Content and Fatty Acid Profile of Ten New Camellia oleifera Cultivars. (31st January 2016) - Yang, Chunying; Liu, Xueming; Chen, Zhiyi; Lin, Yaosheng; Wang, Siyuan
Abstract : The oil contents and fatty acid (FA) compositions of ten new and one wild Camellia oleifera varieties were investigated. Oil contents in camellia seeds from new C. oleifera varied with cultivars from 41.92% to 53.30% and were affected by cultivation place. Average oil content (47.83%) of dry seeds from all ten new cultivars was almost the same as that of wild common C. oleifera seeds (47.06%). New C. oleifera cultivars contained similar FA compositions which included palmitic acid (C16:0, PA), palmitoleic acid (C16:1), stearic acid (C18:0, SA), oleic acid (C18:1, OA), linoleic acid (C18:2, LA), linolenic acid (C18:3), eicosenoic acid (C20:1), and tetracosenoic acid (C24:1). Predominant FAs in mature seeds were OA (75.78% 81.39%), LA (4.85% 10.79%), PA (7.68% 10.01%), and SA (1.46% 2.97%) and OA had the least coefficient of variation among different new cultivars. Average ratio of single FA of ten artificial C. oleifera cultivars was consistent with that of wild common C. oleifera . All cultivars contained the same ratios of saturated FA (SFA) and unsaturated FA (USFA). Oil contents and FA profiles of new cultivars were not significantly affected by breeding and selection.